Rediseño de las instalaciones eléctricas en el complejo turístico “EL TRUCHON” mediante el estudio comparativo de normas. - Cunalata Ponluisa, Oscar Alexis (2021)
This research project was carried out in the Valle Hermoso sector of San Pedro de Pelileo city, Tungurahua province with the aim of redesigning the electrical installations within the “El Truchon” Tourist Complex through the application of electrical regulations. In order to carry out the electrical redesign, the current information of the complex was collected, determining the problematic and unsafe facts in the electrical installations, through the technical visit it was concluded that the system was not suitable for use. For this reason, in this research project, mention is made of two design standards for commercial electrical installations that will be used and these are: the IEEE Std. 241-1990 Recommended Practice for Electric Power System in Commercial Buildings and the RD 842_2002 standard of Electrotechnical Regulation For low voltage, both standards help in the synthesis of the main calculations of electrical installations, using regulatory formulas and tables in a simple way, in which once the analysis of each of the standards has been carried out, a comparison between them is established.